Annual Plan 1965-66 Planning Commission - Planning Commission (Planning Commission, 1965)
The outlay envisaged for the State Third Plan originally was Rs 231.39 crores and against this the anticipated expenditure 1961-65 was Rs 186.43 crores. This would leave a balance of only Rs 44.96 crores for 1965-66 while the anticipated expenditure in 1964-65 was Rs 63.39 crores. It was considered that it would be a most unsatisfactory position if the Plan for 1965-66 were to be so much lower in size than that for 1964-65 ; in the normal course the tempo of developmental activities should increase over the successive years of the Plan, particularly the last year whereas with the balance left for 1965-66 the departments would find it impossible even to continue all the existing schemes.
Planning Commission